Evaluation of Tax Consultant Information System - Kusumastuti, H; Nur, T F; Kasim, E; Widodo, A (KnE Social Sciences, 2018)
The role of a tax consultant to support government-enhancing taxpayers’ compliance is significant in carrying out their rights and obligations, which will ultimately have an impact on the government income. There is a huge gap between the number of taxpayers and the tax consultants, therefore, the government is expected to enhance the role of tax consultants in order to obtain valid source of data and information. The Evaluation of Information Systems Service Tax Consultants (SIKOP) is a Tax Consultant Information System designed to meet those requirements. The SIKOP was conducted to determine the quality of the service of the SIKOP with the Service Quality (SERVQUAL) model, through the dimensions of tangibles, realibility, responsiveness, assurance and empathy. The research method used is a descriptive approach. Primary data were obtained through questionnaire, direct interview to informants and direct observation (observation) on the incidence in the field, while the secondary data were obtained from the published literature and related documents. Keywords: e-Government, Tax Consultants, Service Quality (SERVQUAL)